2020
DOI: 10.3389/fneur.2020.00511
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Exhibit Divergent Sex-Based Responses in Transcription and Motor Function After Traumatic Brain Injury

Abstract: Every year, millions of people in the US suffer brain damage from mild to severe traumatic brain injuries (TBI) that result from a sudden impact to the head. Despite TBI being a leading cause of death and disability worldwide, sex differences that contribute to varied outcomes post-injury are not extensively studied and therefore, poorly understood. In this study, we aimed to explore biological sex as a variable influencing response to TBI using Drosophila melanogaster as a model, since flies have been shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 105 publications
(143 reference statements)
2
36
1
Order By: Relevance
“…Several studies in experimental models of brain injury have shown structural and functional damage to mitochondria being an early event in TBI which leads to activation of cell death pathways ( Fischer et al, 2016 ). In a previous study, we demonstrated an upregulation in gene transcription involved with immune response, cytoskeleton organization and apoptosis after injury in Drosophila ( Shah et al, 2020 ). Moreover, we have also shown sex-differences in mitochondrial stress and gene transcription in response to TBI ( Shah et al, 2020 ).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Several studies in experimental models of brain injury have shown structural and functional damage to mitochondria being an early event in TBI which leads to activation of cell death pathways ( Fischer et al, 2016 ). In a previous study, we demonstrated an upregulation in gene transcription involved with immune response, cytoskeleton organization and apoptosis after injury in Drosophila ( Shah et al, 2020 ). Moreover, we have also shown sex-differences in mitochondrial stress and gene transcription in response to TBI ( Shah et al, 2020 ).…”
Section: Resultsmentioning
confidence: 83%
“…Expression analysis was conducted in collaboration with the Wayne State University Genome Sciences Core. Three biological replicates were used for each condition ( Shah et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, this demonstrates sex differences following recovery from TBI and substantiates the importance of using both sexes in preclinical animal models. Interestingly, sex-dependent differences in function (climbing behavior) in fly head injury models has only been examined once prior, in which no differences between sex were revealed [43]. However, flies were only measured for 72 hours during the post-injury period, and the method for measuring behavior was done using the traditional approach to measure startle-induced climbing performance [53,54].…”
Section: While Fruit Flies Are Anatomically Different From Human It mentioning
confidence: 99%
“…Fruit flies represent an excellent tractable model organism to dissect fundamental cellular and molecular disease mechanisms, including neurodegeneration [34][35][36], while taking advantage of their relatively short lifespan [37][38][39][40][41][42] that enables long-term outcome analyses related to head injury exposure. Several fly models have been developed to study traumatic brain injury in Drosophila, but the lack of controlled head-specific impacts may confound neuronalspecific responses [43][44][45]. Head-specific impact models have recently been developed in which physical head impacts were delivered to the heads of individually restrained flies [46][47][48], but no long-term study was carried out to examine the detrimental effects that might develop late in life.…”
Section: Introductionmentioning
confidence: 99%